Faktor Penyebab Nyeri Punggung Bawah pada Ibu Hamil Trimister II dan III di Puskesmas Sumarorong Kabupaten Mamasa Tahun 2024 - Vinny Alvionita; Nunung Erviany; Nopina Palin; Andi Sri Hastuti Handayani Usman (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Lower back pain is a complaint that often occurs in pregnant women in the second and third trimesters. Back pain occurs due to changes in pregnancy hormones which increase levels of the hormone relaxin, this affects the flexibility of the ligament tissue which ultimately increases joint mobility in the pelvis and will have an impact on spinal and pelvic instability and cause discomfort. Based on a preliminary study at the Sumarorong Community Health Center, it was found that the number of pregnant women in the second trimester was 72 and 70 in the third trimester in the working area of ​​the Sumarorong Community Health Center, Mamasa Regency. From this data, there were 22 (30%) pregnant women in the second trimester who experienced back pain, and there were 35 (30%) pregnant women in the second trimester. 50%) third trimester pregnant women experience back pain. Researchers are interested in conducting research on the factors that cause lower back pain in pregnant women in the second and third trimesters in the work area of ​​the Sumarorong Community Health Center, Mamasa Regency in 2024. The research method used is a cross-sectional study. Conducted at the Sumarorong Community Health Center, Mamasa Regency in July – August 2024. The population in this study was all 138 pregnant women in the second and third trimesters at the Sumarorong Community Health Center with a total sample of 57 pregnant women. The results of the study showed that there was a significant relationship between age, education, occupation and gestational age with back pain with each p value = 0.000.